(untitled) (REMUNOM, 2024)
This article aims to bring a better understanding of the institute of disregard for legal personality in the context of Brazilian civil proceedings. However, this instrument, essential to the legal order, was created to allow the liability of the personal assets of partners and/or company administrators in cases where there is abuse, fraud, misuse of purpose, or confusion of assets within the legal personality. This procedure emerged in the last century, around the sixties, due to repeated fraudulent practices involving companies, and gained prominence, a few years later, in the Consumer Protection Code of 1990 and the Civil Code in 2002, providing even more security to the national legal system. For its application, it is necessary to demonstrate abuse of legal personality, evidenced by misuse of purpose or confusion of assets. The procedure is initiated upon request from the interested party, following the rules of the Civil Procedure Code. This measure is crucial to protect creditors and hold those who caused damage accountable, promoting justice and integrity in the legal system. Given its objective, it contributes to the effectiveness of the principle of the company’s social function, helping to resolve legal demands, and being an important tool that guarantees effectiveness in combating fraud and abuse. Its procedure, although complex, is important and ensures the rights of creditors, helping to maintain the integrity and legal security of the Brazilian judicial system.